Italian consensus conference on management of uterine sarcomas on behalf of S.I.G.O. (Societa' italiana di Ginecologia E Ostetricia). (November 2020) - Ferrandina, Gabriella; Aristei, Cynthia; Biondetti, Pietro Raimondo; Cananzi, Ferdinando Carlo Maria; Casali, Paolo; Ciccarone, Francesca; Colombo, Nicoletta; Comandone, Alessandro; Corvo', Renzo; De Iaco, Pierandrea; Dei Tos, Angelo Paolo; Donato, Vittorio; et al.
Abstract: Background: Uterine sarcomas are very rare tumours with different histotypes, molecular features and clinical outcomes; therefore, it is difficult to carry out prospective clinical trials, and this often results in heterogeneous management of patients in the clinical practice. Aim: We planned to set up an Italian consensus conference on these diseases in order to provide recommendations on treatments and quality of care in our country. Results: Early-stage uterine sarcomas are managed by hysterectomy + bilateral salpingo-oophorectomy according to menopausal status and histology; lymphadenectomy is not indicated in patients without bulky nodes, and morcellation must be avoided. The postoperative management is represented by observation, even though chemotherapy can be considered in some high-risk patients. In early-stage low-grade endometrial stromal sarcoma and adenosarcomas without sarcomatous overgrowth, hormonal adjuvant treatment can be offered based on hormone receptor expression. In selected cases, external beam radiotherapy ± brachytherapy can be considered to increase local control only. Patients with advanced disease involving the abdomen can be offered primary chemotherapy (or hormonal therapy in the case of low-grade endometrial stromal sarcoma and adenosarcoma without sarcomatous overgrowth), even if potentially resectable in the absence of residual disease in order to test the chemosensitivity (or hormonosensitivity); debulking surgery can be considered in patients with clinical and radiological response. Chemotherapy is based on anthracyclines ± ifosfamide or dacarbazine. Palliative radiotherapy can be offered for symptom control, and stereotactic radiotherapy can be used for up to five isolated metastatic lesions. Conclusions: Treatment of uterine sarcoma should be centralised at referral centres and managed in a multidisciplinary setting. Highlights: The consensus conference analysed many issues relative to uterine sarcoma management. The member panel provided recommendations based on the level of available evidence. Uterine sarcoma should be managed in referral centres by multidisciplinary boards.